Ixodes ticks belonging to the Ixodes ricinus complex encode a family of anticomplement proteins - Daix, V.; Schroeder, H.; Praet, N.; Georgin, J.-P.; Chiappino, I.; Gillet, L.; de Fays, K.; Decrem, Y.; Leboulle, G.; Godfroid, E.; Bollen, A.; Pastoret, P.-P.; et al. (My University, 2007)
The alternative pathway of complement is an important innate defence against pathogens including ticks. This component of the immune system has selected for pathogens that have evolved countermeasures. Recently, a salivary protein able to inhibit the alternative pathway was cloned from the American tick Ixodes scapularis (Valenzuela et al., 2000; J. Biol. Chem. 275, 18717–18723). Here, we isolated two different sequences, similar to Isac, from the transcriptome of I. ricinus salivary glands. Expression of these sequences revealed that they both encode secreted proteins able to inhibit the complement alternative pathway. These proteins, called I. ricinus anticomplement (IRAC) protein I and II, are coexpressed constitutively in I. ricinus salivary glands and are upregulated during blood feeding. Also, we demonstrated that they are the products of different genes and not of alleles of the same locus. Finally, phylogenetic analyses demonstrate that ticks belonging to the Ixodes ricinus complex encode a family of relatively small anticomplement molecules undergoing diversification by positive Darwinian selection.
Keywords: ticks; Ixodes ricinus; salivary glands; anticomplement; immune evasion